POLA PRILAKU KONSUMSI MUSLIMAH GENERASI Z TERHADAP PRODUK TREND FASHION (STUDI KASUS MAHASISWI UIN IMAM BONJOL) - Anggraini, Misi; Nusrida, Helda; Kamarni, Neng (Universitas Negeri Surabaya, 2022)
Generation Z is a generation in the digitalization era that always interacts with technology. Generation Z is a generation that is easily influenced by the times, including generation Z Muslim women. The influence of the times also affects the consumption pattern of Muslim generation Z towards fashion trend products. Writing this article aims to analyze how the consumption pattern of generation Z Muslim women on fashion trend products. The research was conducted using qualitative research methods with a case study research approach, data analysis used was a case study with data collection techniques through interviews, observation and also distributing questionnaires via google form. The results of the study show that Muslim women of generation Z follow the development of fashion trend products but still follow shari'ah rules in choosing fashion trends according to shari'ah rules. However, in terms of following the ever-changing fashion trends, needs change into momentary desires. Then it has the impact of israf, tabzir, riya, and tabarruj attitudes on generational consumption patterns, especially among UIN Imam Bonjol Padang students.